Fourteen-day vonoprazan and low- or high-dose amoxicillin dual therapy for eradicating Helicobacter pylori infection: A prospective, open-labeled, randomized non-inferiority clinical study - Hu, Yi; Xu, Xin; Liu, Xiao-Shun; He, Cong; Ouyang, Yao-Bin; Li, Nian-Shuang; Xie, Chuan; Peng, Chao; Zhu, Zhen-Hua; Xie, Yong; Shu, Xu; Zhu, Yin; et al. (Frontiers in Immunology, 2023)
Background and aim We previously reported that vonoprazan-amoxicillin (VA) dual therapy for 7 or 10 days is not satisfactorily efficacious for Helicobacter pylori (H. pylori) eradication. We aimed to explore the efficacy of VA dual therapy for 14 days as a first-line treatment for H. pylori infection. Methods This was a single center, prospective, open-labeled, randomized non-inferiority clinical study conducted in China. Treatment naïve H. pylori infected patients were randomized into two groups: 20 mg vonoprazan (VPZ) b.i.d. in combination with low-dose (1000 mg b.i.d.) or high-dose (1000 mg t.i.d) amoxicillin for 14 days. 13C-urea breath tests were used to access the cure rate at least 4 weeks after treatment. Results A total of 154 patients were assessed and 110 subjects were randomized. The eradication rate of VPZ with b.i.d. amoxicillin or t.i.d. amoxicillin for 14 days was 89.1% and 87.3% by intention-to-treat analysis, respectively, and 94.1% and 95.9% by per-protocol analysis, respectively. The eradication rate and incidence of adverse events were not different between the two groups. Conclusion VPZ with b.i.d. or t.i.d. amoxicillin for 14 days provides satisfactory efficacy as a first-line treatment for H. pylori infection in China.